Volleyball in school physical education and student difficulties: Analysis based on tactical principles - Parente, Thomás Augusto [UNESP]; Ginciene, Guy; Impolcetto, Fernanda Moreto [UNESP] (My University, 2020)
Volleyball, as one of the most practiced sport in Physical Education classes in Brazil, is mostly still taught in a traditional model. In order to be teach through games, according to the approaches of Sport Pedagogy, it is understood as necessary analyze students’ behavior during volleyball games in Physical Education (PE) classes. The purpose of this article was to diagnose students’ difficulties in the practice of volleyball in school PE classes, according to the tactical principles of the sport, and to compare them with teachers’ understanding of the discipline. This qualitative research was developed in two stages: a) observation of 14 hours/class PE volleyball classes in two different schools and field diary records of students’ difficulties during the game according to the tactical principles of the sport; and b) application of a Lickert scale with active PE teachers to classify such problems. In the first stage, the following situations were identified as difficulties, in decreasing order of occurrence in the observations: building the attack, occupying spaces on the court, looking for empty spaces, intending to contact the ball, and directing serves. In the teachers’ view, however, difficulties in serves were indicated as students’ main problem and, on the other hand, occupying court spaces as the action they performed more easily. On this basis, it is concluded that there are differences between the researcher’ and the teachers’ views, possibly related to teachers' initial training and previous experiences based on the traditional model, whose focus is not on the teaching of tactical principles.
Keywords: Internal logic; Sport Pedagogy; Sports diagnose; Students’ difficulties.